Design and Implementation of Efficient FIR Filter Structures using Xilinx System Generator - , Gopal S. Gawande, Suraj R. Gaikwad (International Journal of Scientific Research and Management (IJSRM), 2017)
In this paper we propose the design and development of digital filters for audio application using Xilinx System Generator. Digital Filters are important elements in Digital Signal Processing (DSP). In this case, we can decimate the high frequency signal (128 KHz) upto respective low frequency signal (3.4 KHz). Also we introduced some designs of digital filters using MATLAB Simulink model and Xilinx System Generator and compare their respective results in case of computation and storage requirement. The proposed technique is centered on the FIR filtering technique for decimation of audio signal.